Realizing an impressive red-emitting Ca9MnNa(PO4)7 phosphor through a dual function based on disturbing structural confinement and energy transfer. Issue 1 (4th December 2019) - Wang, Jindi; Shang, Mengmeng; Cui, Min; Dang, Peipei; Liu, Dongjie; Huang, Dayu; Lian, Hongzhou; Lin, Jun
Abstract : A dazzling red light was achieved in the Ca9 MnNa(PO4 )7 :Eu 2+ phosphor based on disturbing structural confinement and energy transfer. Abstract : In the field of white LEDs, the research and development of red phosphors have been confronting a challenge. In this paper, a novel red-emitting Ca9 MnNa(PO4 )7 (CMNPO) phosphor, whose emission was attributed to the 4 T1 ( 4 G)– 6 A1 ( 6 S) transition of Mn 2+ ions, was prepared by a high-temperature solid-state reaction. We utilized a chemical co-substitution strategy to optimize the luminescence properties and realize an impressive red emission in our CMNPO phosphor. The introduction of Zn 2+ /Mg 2+ into CMNPO could break the intrinsic structural confinement of Mn 2+, which improved the red emission from Mn 2+ in the narrow confines. The novelty of this work lies in realizing an efficient red phosphor by doping trace amounts of Eu 2+ . By partially replacing Mn 2+ ions with trace amounts of Eu 2+, we obtained a CMNPO phosphor that emitted a dazzling red light, and the quantum yield reached up to 82%. The intensity dependence of this red emission on the trace amounts of doped Eu 2+ was quantitatively analyzed. The substitution of Eu 2+ ions played a dual role in improving the luminescence properties, not only disturbing the structural confinement of Mn 2+ but also transferring energy to Mn 2+ efficiently. By employing it as a red phosphor, we fabricated various high-performance white LEDs with low correlated color temperatures (4642–4956 K) and high-color-rendering indices (80.5–83.4). These findings show the potential promise of the CMNPO phosphor as a red phosphor in warm white LEDs and open up new avenues for the exploration of novel red-emitting phosphors.